Association of sleep duration with chronic constipation among adult men and women: Findings from the National Health and Nutrition Examination Survey (2005–2010) - Yang, Shuai; Li, Shou-Zhen; Guo, Fu-Zheng; Zhou, Dong-Xu; Sun, Xiao-Feng; Tai, Jian-Dong (Frontiers in Neurology, 2022)
Background: Previous studies suggested that unhealthy sleep patterns were closely associated with gastrointestinal diseases, but the impact of unhealthy sleep duration on chronic constipation has not been well studied until now. In this study, we aim to explore the association between sleep duration and constipation among males and females. Methods: We utilized the US National Health and Nutrition Examination Surveys data from 2005 to 2010, and adults (≥20 years old) who completed the sleep and bowel health questionnaires were enrolled in this observational study. Sleep duration was categorized into four groups: very short sleep (<5 h/night), short sleep (5-6 h/night), normal sleep (7-8 h/night), and long sleep (≥9 h/night). Chronic constipation was defined as Bristol Stool Scale Type 1(separate hard lumps, like nuts) or Type 2(sausage-like but lumpy). Controlling demographic, lifestyle, and dietary factors, the logistic regression model in Generalized Linear Model (GLM) function was used to estimate the correlation of sleep duration with constipation among men and women. Results: Of the 11785 individuals (51.2% males and 48.8% females), 4.3% of men and 10.2% of women had constipation, respectively. More than half of patients with constipation did not adopt the recommended sleep duration. Compared with normal individuals, male participants with constipation had a higher proportion of shorter sleep duration (41.0% vs. 32.3% in the short sleep group and 6.3% vs. 4.7% in the very short sleep group), and female individuals with constipation had a higher proportion of long sleep duration (12.7% vs. 8.2%). After covariates adjustment, men with short sleep duration (5-6 h/night) correlated with increased odds for constipation (OR:1.54, 95%CI:1.05-2.25), and women with long sleep duration (≥9 h/night) linked to the higher constipation risk (OR:1.58, 95%CI:1.10-2.29). Excessive sleep duration in males or insufficient sleep duration in females was neither linked to increased nor decreased constipation risk. Conclusions: In this observational study of a nationally representative sample of adults, we demonstrate a differential impact of unhealthy sleep duration on constipation among men and women. Short sleep duration poses a higher risk of constipation in men, and excessive sleep duration correlates with higher constipation risk in women.